The Russian war on Ukraine and its repercussions on the Middle East - Ibrahim, Dr. Ibrahim Harbi (The journal of contemporary issues in business and government, 2023)
The aim of the research is to analyze the Russian war on Ukraine, its causes, the factors for the rise of the crisis and its evolution towards war, and to identify the driving forces of the crisis, as well as the repercussions of the Russian war on Ukraine on the Middle East region, including the repercussions on the Arab Gulf states and Iran, leading to the most prominent scenarios of the Russian war on Ukraine. The research problem centered on the fact that the repercussions of the Russian war on Ukraine were not confined to Europe, but were affected by the Middle East region, as the region is a neighbor of Ukraine, separated from it only by a distance of about a thousand kilometers. On the economic level, some countries in the region are also very close to Ukraine and Russia as trading partners, and therefore, the effects of the crisis will be tangible, albeit to varying degrees, on the economies of the region. It may have multiply negative consequences on levels of food security and well-being across the region, in addition to the Corona pandemic, disruption of supply chains, and internal problems specific to each of its countries. The consequences of this war will affect the energy sector in the Middle East, as it may urge the United States, in light of The crisis urged its partners, Saudi Arabia and Qatar, to increase energy supplies to Europe in the event that Russia decided to stop supplying it with these resources. The research came out with several scenarios for the Ukrainian scene, and the proposed scenarios do not contradict each other, and may intersect and lead to a different result. But no matter how this war ends, the world will change after that, and it will not return to the way it was before. Russia's relationship abroad will be different. The Europeans' handling of security issues will be different.